Pediatric Cardiac Service Development in Croatia - Malčić, Ivan; Anić, Darko (Frontiers in Cardiovascular Medicine, 2022)
This article describes the establishment of a pediatric cardiac service program in a limited resource country. According to national epidemiological studies about 330 children with congenital heart disease (CHD) are born every year in Croatia. As a part of the former Yugoslavia, there was not an organized strategy for the pediatric cardiac service. After Croatian independence in 1991, even during the war, a need for such service led to the first step in development of organized care for CHD patients, a humanitarian mission provided by non-governmental organization (NGO), from USA. In the ten-year period (1993-2003), 601 children were operated on during this program. After the end of this program, the Croatian team was not able to cover the whole spectrum of pediatric cardiac care independently. About 60% of the children were sent abroad, and only about 40% of the operations were performed in Croatia. Over the time, the surgical team improved and after a specialized congenital heart surgeon joined, the number and quality of the program in the country raised, and the number of referrals to foreign centers gradually declined. In the meantime, cardiological interventional program also improved. Today majority of standard congenital heart surgery procedures can be performed in Croatia. Last year our congenital heart team operated 180 patients on with low mortality and the interventional team (pediatric and adult) performed 66 procedures. In the article, we present positive shifts achieved during time as well as weaknesses and reasons for problems in establishing a high-quality CHD center.